Influence of different semiarid zones of Hidalgo in wild xoconostle prickly pear morphometry - Ruiz-Juárez, Daniel; Guitiérrez-Rojas, Mónica; Ortega-Rojas, Jesús; Rueda-Puente, Edgar Omar; Ceiro-Catasú, Wilson Geobel; Holguín-Peña, Ramón Jaime (Journal of the Professional Association for Cactus Development, 2024)
The transcendence of wild xoconostle prickly pear species -wild or cultivated in semi arid zones- dates to its Mexican origin, historical, gastronomic, cultural and medicinal customs and potentially a product of interest for rural areas due to its demand in regional and international markets. A few studies have been carried out on climate influence and arid conditions on fruit quality and no regulations exist, which allows more competitive advantages in the market. The objective of this study was to know the impact of different characteristics of arid zones, specially on morphometric differentiation in wild xoconostle prickly pear species. The study was performed in three cardinal points, Northeastern, Southern and Western of Mezquital Valley, Hidalgo, Mexico. A total of 1,000 fruits were collected, 25 and 10 per location with four replications. The morphometric variables evaluated were fruit shape and weight, equatorial and longitudinal diameter, shell thickness, areole density, developed seed number, fruit surface color uniformity, juiciness and pulp color. Three main xoconostle variants were found geographically and identified according to the region. In the northeast, Opuntia matudae (cv. Blanco) predominates in spherical prickly pear shape; in the West, a greater O. matudae (cv. Cuaresmeño) abundance is observed with predominant characteristics from elongated to ovoid shapes; in the South, more predominant O. joconostle (burrona type) is observed with a typical elliptical fruit shape. The morphometric characteristics in fruit showed significant differences among sites (P ? 0.01); O. joconostle had higher values in quantitative variables, unlike O. matudae Blanco and Cuaresmeño. The semi-arid zone impact in Valle del Mezquital have influenced the morphometric characterization of wild xoconostle prickly pear species.